Proceedings of the 54th Annual Meeting of the Association for Computational Linguistics (Volume 1: Long Papers) 2016
DOI: 10.18653/v1/p16-1048
|View full text |Cite
|
Sign up to set email alerts
|

CSE: Conceptual Sentence Embeddings based on Attention Model

Abstract: Most sentence embedding models typically represent each sentence only using word surface, which makes these models indiscriminative for ubiquitous homonymy and polysemy. In order to enhance representation capability of sentence, we employ conceptualization model to assign associated concepts for each sentence in the text corpus, and then learn conceptual sentence embedding (CSE). Hence, this semantic representation is more expressive than some widely-used text representation models such as latent topic model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 18 publications
(16 reference statements)
1
19
0
Order By: Relevance
“…Wellknown examples include word2vec (Mikolov et al, 2013), GloVe (Pennington et al, 2014), or fastText . Approaches for learning sentence embeddings have also been introduced, including SkipThought (Kiros et al, 2015), ParagraphVector (Le and Mikolov, 2014), Conceptual Sentence Embedding (Wang et al, 2016), Sequential Denoising Autoencoders (Hill et al, 2016) or Fast-Sent (Hill et al, 2016). In a comparison of unsupervised sentence embedding models, Hill et al (2016) show that the optimal embedding critically depends on the targeted downstream task.…”
Section: Related Workmentioning
confidence: 99%
“…Wellknown examples include word2vec (Mikolov et al, 2013), GloVe (Pennington et al, 2014), or fastText . Approaches for learning sentence embeddings have also been introduced, including SkipThought (Kiros et al, 2015), ParagraphVector (Le and Mikolov, 2014), Conceptual Sentence Embedding (Wang et al, 2016), Sequential Denoising Autoencoders (Hill et al, 2016) or Fast-Sent (Hill et al, 2016). In a comparison of unsupervised sentence embedding models, Hill et al (2016) show that the optimal embedding critically depends on the targeted downstream task.…”
Section: Related Workmentioning
confidence: 99%
“…Trends over time between visualization and data mining are revealed through spark lines appearing beside the concept label. Since the total number varies widely across concepts, we normalized the spark lines for each concept so that they reveal the relative number of papers [327], [335], [339] word/phrase/entity-level (679) [4], [286], [289] document-level (288) [14], [252], [376] hybrid (387) [40], [155], [349] model inference (1335) non-probabilistic inference (267) [91], [101], [336] probabilistic inference (1160) [185], [198], [360] modeling (3085) models for classification (1636) [45], [176], [216] models for clustering (908) [300], [301], [361] models for dimension reduction (247) [129], [221], [287] topic models (1089) [32], [33], [139] models for regression (256) [49], [149], [298] language model (271) [24], [89], [158] graphical models (187) [262], [268], [367] neural networks (412) [175], [193], [224] mixture models (128)…”
Section: Visualization Of Concept Relationsmentioning
confidence: 99%
“…E.g., [19] introduced an entity-level masking strategy to ensure that all of the words in the same entity were masked during word representation training, instead of only one word or character being masked; [20] updated contextual word representations via a form of wordto-entity attention, by inserting prior knowledge into a deep neural model. On the other hand, previous work has demonstrated that, leveraging extra lexical knowledge (e.g., concept etc.,) can significantly boost the efficiency of contextualized embeddings for word [15], entity [21], relation [22], sentence [23], and so on. Overall, the lexicon-enhanced contextualized embedding representation produced by these models has produced substantial gains in a number of downstream NLP tasks.…”
Section: Related Work and Motivation A Unsupervised Pre-trainingmentioning
confidence: 99%